Regulation of noradrenaline synthesis, uptake, and degradation in the left ventricle by fatty acid amide hydrolase (FAAH) inhibitor URB597 in the chronic unpredictable stress model of depression - Ferizović Harisa; Spasojević Nataša; Janković Milica; Stefanović Bojana; Dronjak Slađana (Archives of Biological Sciences)
Depression has been linked to the dysfunction of the autonomic nervous system, which may cause dysregulation of the cardiovascular system. One promising therapeutic strategy for treating different diseases is inhibiting the enzyme fatty acid amide hydrolase (FAAH), which increases the availability of endogenous cannabinoids. We examined the effect of chronic FAAH inhibition with URB597 treatment on the noradrenaline (NA) content, synthesis, transport, and degradation in the left ventricle of female and male rats exposed to chronic unpredictable stress (CUS). CUS decreased the levels of both NA and dopamine-β-hydroxylase (DBH) protein in male rats and decreased NA transporter (NET) protein levels in female rats while elevating monoamine oxidase A (MAO-A) in both sexes. Intraperitoneal URB597 application led to increased expression of DBH in stressed males, as well as elevated NET protein levels and decreased MAO-A protein levels in the left ventricle of stressed rats of both sexes. URB597 treatment may have a beneficial effect on the cardiovascular system in an animal model of depression with heightened sympathoneural activity.